THE USE OF ACTIVE GAMES IN DEVELOPING VOLLEYBALL SKILLS AMONG 5TH–6TH GRADE SCHOOL STUDENTS (World Bulletin of Physical Education and Sports Science, 2026)
This scientific article substantiates the pedagogical significance of using active games in developing volleyball element skills (overhead pass, underhand reception, ball throwing, positioning, and movement) among 5th–6th grade students. The study examines age characteristics, physical and psychophysiological development factors, the advantages of the game method, and proposes a system of specially designed active games applied during lessons. Furthermore, the results of experimental research are analyzed, and the positive impact of active games on the effective formation of volleyball technical elements is identified.
Keywords: Volleyball, active games, 5th–6th grade, technical skills, physical education, pedagogical technology, coordination, speed, agility.